(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The purpose of this paper is to identify the factors determining the growth of the regional economy. The research of the influence of the main determinants of economic growth has been executed in the paper: labor force, investments into fixed capital, R & D expenditure on the index of regions’ economy growth. The analysis shows that all these factors made an essential impact on the rates of increase of economy of regions in 2000-2008. Estimating the prospects of the growth of economy of regions in strategic prospect (till 2020) it is necessary to notice that possibilities of the growth at the expense of extensive factors are almost set. In these conditions a steady growth of regional economy is possible only at the expense of an intensification of investment process and strengthening of its innovative component.